Studies on effect of size on strength and ductility of RC deep beams - Rao, G. Appa; Kunal, K. (Journal of Structural Engineering, 2025)
This paper reports on some experimental investigations on the shear strength and shear ductility of reinforced concrete deep beams. The variables in the study are; depth of beam and the quantity of shear reinforcement. Twelve beams of depth 250mm, 500mm and 750mm with shear span-to-depth (a/d) ratio 1.5 and span-to-depth ratio (l/d) 3.0 made of 60MPa concrete were tested under three-point loading. The post-peak load-deflection response, shear strains, shear crack width, shear ductility and reserve shear strength are the parameters studied. It has been observed that the modes of failure in deep beams are influenced by the size of beam and quantity of shear reinforcement. The shear strength of deep beams decreases as the size of the beam increases. However, the large size beams showed relatively brittle behavior. Sufficient quantity of shear reinforcement in large size beams altered the brittle failure in to ductile. The post-peak load-deflection response of small beams was found to be gradual with heavy shear reinforcement. The diagonal strains and the diagonal crack widths in shear span increase as the web (shear) reinforcement increases. The shear ductility of beams decreases as the depth of beam increases, which showed higher values with higher shear reinforcement. Significant reserve strength has been achieved after diagonal cracking with higher shear reinforcement.